The episode of the Sirens in Apollonius of Rhodes’ Argonauts: Comic enrichment and metapoetic aspects (2021)
Just as in the Odyssey the hero on his return journey must resist the charm of the Sirens, in Argonauts the heroes must also overcome them on their return to Hélade. Although bibliographic studies note a change in tone between the Homeric model and the Apollonian text (from sinister to humorous and erotic), we consider that they have not acknowledged its important metapoetic value. According to our reading, the confrontation between Orpheus and the Sirens through song represents the relationship of the new poem with tradition and takes  up the meanings and functions of the Odyssey episode, where a clear dispute arises between Odyssey and Iliad, as the classic article by Pucci (1979) shows. In this sense, it is important to highlight not only the tone, but also the presence of a comic diction in the Apollonian episode, which represents the non-epic character of the Sirens defeated by Orpheus.